Assessing the COVID-19 vaccine hesitancy in the Chinese adults using a generalized vaccine hesitancy survey instrument. Issue 11 (2nd November 2021) - Shen, Xin; Dong, Hao; Feng, Jing; Jiang, Heng; Dowling, Rowan; Lu, Zuxun; Lv, Chuanzhu; Gan, Yong
ABSTRACT: The objectives of this study were to determine coronavirus disease 2019 (COVID-19) vaccination hesitancy and influencing factors in China, while broadening the applicability of the Vaccine Hesitancy Scale (VHS). A cross-sectional survey was conducted in China from 4th to 26th February 2021. Convenience sampling method was adopted to recruit participants. A total of 2, 361 residents filled out the questionnaire. Confirmatory factor analysis was used on the validation set to confirm the latent structure that resulted from the exploratory factor analysis, which was conducted on the construction set. Multiple linear regression model analyses were used to identify significant associations between the identified the revised version of VHS subscales and hypothesized explanatory variables. Two subscales were identified within the VHS through data analysis, including "lack of confidence in the need for vaccines" and "aversion to the risk of side effects." The results indicated that the hesitancy of the participants in our sample was both driven the two mainly aspects. In addition, more than 40% of the participants expressed hesitation in half of the items in VHS. This study characterized COVID-19 vaccine hesitancy in China, and identified disparities in vaccine hesitancy by socio-demographic groups and knowledge about the vaccine. Knowledge of the vaccine was statistically linked to respondents' answers to the clustered 'lack of confidence' and 'risks perception' items. Our results characterize Chinese citizens' COVID-19 vaccine concerns and will inform targeted health communications.